What Did It Take to Scale Up and Sustain Udaan, a School-Based Adolescent Education Program in Jharkhand, India?. Issue 2 (3rd April 2018) - Chandra-Mouli, Venkatraman; Plesons, Marina; Barua, Alka; Gogoi, Aparajita; Katoch, Manju; Ziauddin, Mohammed; Mishra, Rita; Nathani, Vinita; Sinha, Anand
ABSTRACT: Since 2006, Udaan—a school-based adolescent education program in Jharkhand, India—was the only at-scale state-run program in the country. To determine factors that contributed to Udaan's scale-up and longevity, this study drew information from programmatic reports and interviews with the Centre for Catalyzing Change staff. Key factors for Udaan's success included an enabling policy environment, a willing government that supported and operationalized the program, a knowledgeable and committed NGO partner, sustained funding, and a commitment to constant improvement through evaluation. Udaan provides an example of a well-designed, implemented, and evaluated school-based adolescent health program that has been operating at scale over a sustained period. Other programs in India and elsewhere can benefit from learning from Udaan's experience.